2011
DOI: 10.1167/iovs.11-7292
|View full text |Cite
|
Sign up to set email alerts
|

Copy-Number Variations inEYS:A Significant Event in the Appearance of arRP

Abstract: This is the first report of a systematic CNV screening of EYS gene in a cohort of arRP patients. Results suggest that midsized genomic rearrangements in EYS gene would be a common event in the appearance of RP phenotype. An efficient and cost-effective strategy validating a novel MLPA kit as a complementary diagnostic method for EYS pathogenic evaluation has been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 15 publications
3
39
1
Order By: Relevance
“…We found that one of the pathogenic EYS alleles was a large SV (446 kb) with a complex genomic rearrangement. This finding supports the notion that SVs represent frequent pathogenic mutations in this gene (17). A homozygous nonsense mutation in exon 6 of DFNB31 was identified in R18, a patient with nonsyndromic ARRP.…”
Section: Discussionsupporting
confidence: 86%
“…We found that one of the pathogenic EYS alleles was a large SV (446 kb) with a complex genomic rearrangement. This finding supports the notion that SVs represent frequent pathogenic mutations in this gene (17). A homozygous nonsense mutation in exon 6 of DFNB31 was identified in R18, a patient with nonsyndromic ARRP.…”
Section: Discussionsupporting
confidence: 86%
“…This is in line with our findings, as bioinformatic analysis of the breakpoint regions suggests nonhomologous end joining or fork stalling and template switching as the most likely mechanisms for this novel deletion (data not shown). Although only a limited number of CNVs have been described in RDs, not surprisingly with low frequencies comparable to other single-base RD mutations, 26,36 their occurrence warrants implementation of a CNV analysis algorithm in addition to IBD data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…25 Subsequent Sanger sequencing of exons with a coverage below 20× did not identify a second mutation. As several copy-number variations (CNV) have been described in EYS, 26 multiplex ligation-dependent probe amplification was performed. However, no CNV was detected.…”
Section: Combined Ibd Mapping and Wesmentioning
confidence: 99%
“…2006; Pieras et al. 2011). It is widely accepted that CNVs, especially deletion alleles, often result in affected phenotypes or increase an individual's susceptibility for the disease (Feuk et al.…”
Section: Introductionmentioning
confidence: 99%